2017
DOI: 10.1038/s41598-017-14977-7
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation of Pirani and Dimeglio Scoring Systems for Ponseti Management at Different Levels of Deformity Severity

Abstract: The Pirani and Dimeglio scoring systems both have excellent inter-observer and intra-observer reliability, but no research has been conducted to determine their inter-observer reliability and their relationship at different levels of deformity. A total of 173 idiopathic clubfoot cases were reviewed using Pirani and Dimeglio scoring systems, and the number of casts needed was also recorded. For clubfeet with a cast number equal to 2 or 7 and 8, the inter-observer reliability of the two scoring systems was poor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 23 publications
3
39
1
Order By: Relevance
“…Therefore, we decided to use the Pirani score in our study. Comparing the determined values for the Pirani score at the beginning of treatment, we found similar results (our results: 4.75, Fan et al: [ 1 ] 4.4, Agarwal et al: [ 19 ] 5.0).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, we decided to use the Pirani score in our study. Comparing the determined values for the Pirani score at the beginning of treatment, we found similar results (our results: 4.75, Fan et al: [ 1 ] 4.4, Agarwal et al: [ 19 ] 5.0).…”
Section: Discussionsupporting
confidence: 89%
“…Idiopathic clubfoot is one of the most prevalent musculoskeletal congenital defects (1-2 per 1000 live births), which is not self-healing. The deformity will deteriorate until adulthood and cause adverse effects for the patient, if early treatment does not occur [1].…”
Section: Introductionmentioning
confidence: 99%
“…Clubfoot management is still challenging in terms of its assessment and intervention methods. The accurate evaluation of clubfoot is essential for assessing the initial severity, choosing the treatment options, monitoring and predicting the progress of the intervention, and predicting relapses of the foot (Wainwright et al, 2002 ; Herd et al, 2004 ; Siapkara and Duncan, 2007 ; Ramanathan and Abboud, 2010 ; Jain et al, 2012 , 2017 ; Fan et al, 2017 ). There are several scoring systems that have been used as assessment tools to evaluate the severity of clubfoot deformity.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies reported that there is no universal standard assessment method available at present to quantify the initial severity of the clubfoot or monitor the clubfoot treatment (Jain et al, 2001 ; Gigante et al, 2004 ; Dyer and Davis, 2006 ; Ramanathan et al, 2009 ; Ramanathan and Abboud, 2010 ; Yapp et al, 2012 ; Bhaskar and Patni, 2013 ). Because it is difficult to obtain the objective measurements from all these classification systems (Catterrall classification system, Pirani scoring, Dimeglio classification system, and Harrold and Walker classification system) due to subjective in nature (Wainwright et al, 2002 ; Jain et al, 2012 , 2017 ; Fan et al, 2017 ). In view of imaging assessment methods, it provides objective details of severities of the clubfoot.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation